2021
DOI: 10.3389/fmicb.2020.545251
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum Promotes the Progression of Colorectal Cancer Through Cdk5-Activated Wnt/β-Catenin Signaling

Abstract: Background/AimsGrowing evidence supports the direct link of Fusobacterium nucleatum with colorectal cancer (CRC). However, to date, the underlying mechanism of action remains poorly understood. In this study, we examined the effects of F. nucleatum on the progression of CRC and investigated whether cyclin-dependent kinase 5 (Cdk5) is involved in the effect through activating the Wnt/β-catenin signaling pathway.Materials and MethodsCRC tissues and matched histologically normal specimens were collected from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…These ndings indicated that Fn could play an important role in the occurrence and development of CRC. We have con rmed in our previous work that at the cellular level, Fn promotes the progression of CRC through the Cdk5-activated Wnt/β-catenin signaling [19]. The experiments of the present study showed that the intestinal ora of mice given Fn gavage mainly included Firmicutes, Bacteroidetes, and Proteobacteria (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…These ndings indicated that Fn could play an important role in the occurrence and development of CRC. We have con rmed in our previous work that at the cellular level, Fn promotes the progression of CRC through the Cdk5-activated Wnt/β-catenin signaling [19]. The experiments of the present study showed that the intestinal ora of mice given Fn gavage mainly included Firmicutes, Bacteroidetes, and Proteobacteria (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…However, we preliminarily showed that nuclear β-catenin translocation by Wnt signaling activation may be closely associated with the enhancement of REG Iα expression in colon cancer cells in vitro. Interestingly, recent studies have suggested that Wnt signaling may be a key pathway for Fn-associated cell growth in colon cancer [11,47,48]. Thus, since REG Iα is able to function as a growth factor [25,26], we would like to speculate that Fn-associated β-catenin-nuclear translocation may play a role in the growth of SSA/P lesions, at least in part, via the growth-promoting effect of REG Iα protein.…”
Section: Discussionmentioning
confidence: 94%
“…Certain studies have reported that Fusobacterium nucleatum , an anaerobic Gram-negative oral commensal bacterium, is important in CRC tumorigenesis and is often associated with metastasis, chemo-resistance and poor prognosis ( 53 , 155 - 157 ). A previous study has suggested that Fusobacterium nucleatum is present in CRC and adheres to and invades intestinal epithelial cells mainly via virulence factors, such as Fusobacterium adhesin A (FadA) ( 53 ).…”
Section: Therapeutic Strategies Targeting Wnt/β-catenin Signaling For Crcmentioning
confidence: 99%
“…However, Ma et al suggested that Fusobacterium nucleatum interacts with E-cadherin leading to EMT instead of β-catenin, which subsequently promotes the malignant phenotype of CRC cells ( 53 ). Another study showed that Fusobacterium nucleatum promotes CRC tumor growth via cyclin-dependent kinase 5 (Cdk5)-activated Wnt/β-catenin signaling and the Cdk5-mediated upregulation of β-catenin, cyclin D1 and c-Myc ( 157 ). Lactobacillus species, another bacterium, inhibits CRC progression via the upregulation of GSK-3β, as well as the downregulation of the Wnt/β-catenin-related genes, such as Axin-2, CTNNB1, cyclin D1, pygopus family PHD finger 2 and inhibitor of DNA binding 2 ( 158 ).…”
Section: Therapeutic Strategies Targeting Wnt/β-catenin Signaling For Crcmentioning
confidence: 99%